2020
DOI: 10.1002/pc.25819
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on enhancement of mechanical and tribological properties of nitrile rubber composites reinforced by different functionalized graphene sheets: Molecular dynamics simulations

Abstract: Molecular dynamics (MD) simulations were adopted to compare the enhanced mechanical and tribological properties of nitrile rubber composites reinforced by different functionalized graphene sheets. Functional groups such as hydroxyl (OH), carboxyl (COOH), and ester (COOCH3) were adopted. The constant strain method was applied to measure the mechanical properties of graphene/nitrile rubber composites. Sandwiched molecular models were developed to investigate the tribological properties of graphene/nitrile rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…25 A strong correlation was observed between the amount of GrF-OH fillers added into the HGrF/Nr nanocomposites and the COF, specific wear rate, and temperature. 17,24 The wear rate decreased from approximately 7.21 × 10 −4 to below 4.58 × 10 −4 mm 3 /Nm due to the filler increase. It was determined that the average COF of HGrF/Nr nanocomposites changed with the addition of GrF-OH to the mixture; this value decreased by approximately 10% at the 4 phr filler ratio.…”
Section: Mechanical Properties Of Rubber-based Hybrid Nanocomposites ...mentioning
confidence: 97%
See 1 more Smart Citation
“…25 A strong correlation was observed between the amount of GrF-OH fillers added into the HGrF/Nr nanocomposites and the COF, specific wear rate, and temperature. 17,24 The wear rate decreased from approximately 7.21 × 10 −4 to below 4.58 × 10 −4 mm 3 /Nm due to the filler increase. It was determined that the average COF of HGrF/Nr nanocomposites changed with the addition of GrF-OH to the mixture; this value decreased by approximately 10% at the 4 phr filler ratio.…”
Section: Mechanical Properties Of Rubber-based Hybrid Nanocomposites ...mentioning
confidence: 97%
“…Cui et al 17 investigated the mechanical and tribological properties of graphene filled NBR composites functionalized with OH, COOH, and COOCH 3 functional groups by molecular dynamic simulations. They found that the hydrogen bond formed between the COOH functionalized graphene particles and the NBR matrix and the strong van der Waals interactions showed the best effect in improving the mechanical and tribological properties.…”
Section: Introductionmentioning
confidence: 99%
“…One such modification is the preparation of rubber-based composites. Rubber composites are extensively utilized in industrial applications as they offer outstanding material properties like chemical, wear, and high-temperature resistance [8]. Different fillers have been introduced to rubber materials to build the rubber composites such as silica, cellulose, chitin, starch, carbon black, etc.…”
Section: Introductionmentioning
confidence: 99%
“…MD is an effective method to deal with the problem without these unnecessary assumptions [ 32 , 33 , 34 ]. It has been widely applied to investigate the interfacial properties between polymer and nanocarbon materials, such as single-layer graphene [ 35 ], double-layered graphene [ 36 ], functionalized graphene [ 37 ], flattened carbon nanotubes [ 38 ], functionalized carbon nanotubes [ 39 ], multi-walled carbon nanotubes [ 40 ], CNT bundles [ 41 ], multi-walled carbon nanotubes [ 42 ], and single-layer diamonds [ 43 ]. The results prove that MD can simulate the interfacial properties with high precision and analyze the underlying toughening mechanism.…”
Section: Introductionmentioning
confidence: 99%